Impact of Biochar Use After Five Years in Vertisol and NPK Fertilization on Yield of Shallot (Allium ascalonicum L.) - Oswaldus Oswaldus; Widowati Widowati; Hidayati Karamina (JURNAL BUDIDAYA PERTANIAN, 2022)
Vertisols are soils that expand when wet but shrivel and harden when dry. Their high clay content can affect soil aeration so that it can interfere with nutrient absorption. Biochar is a soil enhancer that has a longer impact on the sustainability of soil fertility. The aim of this study was to evaluate the residual dose of biochar that had been applied five years previously and NPK fertilizer on the growth and yield of shallots on Vertisol as soil medium. This study was conducted in Tunggulwulung Village, Lowokwaru District, Malang City. The method used a two-factor Randomized Block Design, consisting of biochar residue with 3 doses (0; 250; 500 g per polybag) and NPK fertilization (with and without fertilization). There was a positive impact from the residue of the previous five-year application of biochar on increasing the number of shallot leaves and bulbs on Vertisol.